2020
DOI: 10.1039/d0sc90031a
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Helical orbitals and circular currents in linear carbon wires

Abstract: Correction for ‘Helical orbitals and circular currents in linear carbon wires’ by Marc H. Garner et al., Chem. Sci., 2019, 10, 4598–4608.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, we recently demonstrated that the electronic transmission through even- n cumulenes can be almost as high as that of the equivalent odd- n systems by splitting the helical frontier molecular orbitals using pyramidalized π-donor substituents. Strategies for manipulating the helical electronic structure of cumulenes using substituents is described in detail elsewhere. ,, …”
Section: Results: Even-n Cumulenic Carbon Wiresmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we recently demonstrated that the electronic transmission through even- n cumulenes can be almost as high as that of the equivalent odd- n systems by splitting the helical frontier molecular orbitals using pyramidalized π-donor substituents. Strategies for manipulating the helical electronic structure of cumulenes using substituents is described in detail elsewhere. ,, …”
Section: Results: Even-n Cumulenic Carbon Wiresmentioning
confidence: 99%
“…Strategies for manipulating the helical electronic structure of cumulenes using substituents is described in detail elsewhere. [39][40][45][46][47] ELECTRONIC STRUCTURE. The four frontier molecular orbitals and their eigenvalues are calculated for the [4]cumulene-SMe in Figure 8.…”
Section: Even-n Cumulenic Carbon Wiresmentioning
confidence: 99%
See 3 more Smart Citations